Imaginary potential of heavy quarkonia from thermal fluctuations in rotating matter from holography - Zi-qiang Zhang; Xiangrong Zhu; De-fu Hou (Nuclear Physics B, 2023)
Using AdS/CFT correspondence, we study the imaginary part of heavy quarkonia potential from thermal fluctuations in a strongly coupled plasma. We perform the analysis in a rotating deformed AdS black-hole background. It is shown that the presence of angular velocity decreases the onset of imaginary potential thus enhancing quarkonia dissociation, in agreement with previous findings of the entropic force. Moreover, by increasing angular velocity, the thermal width becomes smaller.